REVITALISASI TEKNOLOGI INFORMASI DAN PENDIDIKAN: Sebuah Tantangan Baru bagi IAIN Ar-Raniry - Yusri M. Daud (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2011)
The world is entering a new phase now. Modernization has ended and we have to think in a new way, because the old way does not work anymore. Putting it another way, we have made a big pragmatic change that we ourselves are not aware of it. The blend between transmission technology and computer has produced an era, called the era of information technology. In addition, in the world of education, information technology is a connecting tool that connects various parts of educational institution so that the institution becomes a comprehensive unit. Educational institution is badly in need of information technology in order to get modern and progressive activities of education.